2020
DOI: 10.1161/circulationaha.119.043581
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Catabolism Promotes Thrombosis Risk by Enhancing Tropomodulin-3 Propionylation in Platelets

Abstract: Background: Branched-chain amino acids (BCAAs), essential nutrients including leucine, isoleucine, and valine, serve as a resource for energy production and the regulator of important nutrient and metabolic signals. Recent studies have suggested that dysfunction of BCAA catabolism is associated with the risk of cardiovascular disease. Platelets play an important role in cardiovascular disease, but the functions of BCAA catabolism in platelets remain unknown. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 48 publications
5
72
0
Order By: Relevance
“…The branched-chain amino acids (BCAAs) leucine, isoleucine, and valine are important resources for energy production and regulators of metabolic and nutrient signals. BCAA catabolism is a regulator of platelet activation, and BCAA dysfunction could be associated with arterial thrombosis risk [42]. Although BCAAs have not yet been reported to be associated with venous thrombosis, in this study, we showed alterations in leucine, valine, alanine, and lipoproteins in the thrombosis group (Figure A1).…”
Section: Discussionmentioning
confidence: 47%
“…The branched-chain amino acids (BCAAs) leucine, isoleucine, and valine are important resources for energy production and regulators of metabolic and nutrient signals. BCAA catabolism is a regulator of platelet activation, and BCAA dysfunction could be associated with arterial thrombosis risk [42]. Although BCAAs have not yet been reported to be associated with venous thrombosis, in this study, we showed alterations in leucine, valine, alanine, and lipoproteins in the thrombosis group (Figure A1).…”
Section: Discussionmentioning
confidence: 47%
“…The aggregation of washed platelets was performed as described previously 15 on a whole-blood lumiaggregometer (Chrono-Log, Havertown, PA) upon stimulation with the indicated agonists including thrombin, ADP, U46619, and collagen. Platelet spreading was performed as before.…”
Section: Methodsmentioning
confidence: 99%
“…Tropomodulin was originally discovered to be a protein that binds with tropomyosin to regulate the polymerization and depolymerization of actin (Weber, Pennise et al, 1994). Studies have suggested that the propionylation of TMOD3 is associated with platelet activation and arterial thrombosis (Xu, Jiang et al, 2020). The study pointed out that knocking out TMOD1 in systemic tissues other than the heart caused TG and HDL-C metabolism to be abnormal in mice, and this may be a cause of AS (Ding & Xu, 2015).…”
Section: Discussionmentioning
confidence: 99%